2014
DOI: 10.1128/iai.01634-13
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia pseudotuberculosis Efficiently Escapes Polymorphonuclear Neutrophils during Early Infection

Abstract: The human-pathogenic species of the Gram-negative genus Yersinia preferentially target and inactivate cells of the innate immune defense, suggesting that this is a critical step by which these bacteria avoid elimination and cause disease. In this study, bacterial interactions with dendritic cells, macrophages, and polymorphonuclear neutrophils (PMNs) in intestinal lymphoid tissues during early Yersinia pseudotuberculosis infection were analyzed. Wild-type bacteria were shown to interact mainly with dendritic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 46 publications
(54 reference statements)
3
26
0
1
Order By: Relevance
“…Bioluminescent in vivo imaging (BLI) allows the detection, visual characterization, and semiquantification of bacteria during infection of mice in real time (29). This method has widely been used to monitor Y. pseudotuberculosis YPIII infections using an in vivo imaging spectrum (IVIS) for BLI analysis (30)(31)(32)(33). To allow similar studies in strain IP32953, we constructed bioluminescent variants of the wild-type strain and the ΔtatC and ΔsufI mutant strains by integration of the complete lux operon from Photorhabdus luminescens into the 16S rRNA gene using a thermosensitive plasmid, p16Slux.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioluminescent in vivo imaging (BLI) allows the detection, visual characterization, and semiquantification of bacteria during infection of mice in real time (29). This method has widely been used to monitor Y. pseudotuberculosis YPIII infections using an in vivo imaging spectrum (IVIS) for BLI analysis (30)(31)(32)(33). To allow similar studies in strain IP32953, we constructed bioluminescent variants of the wild-type strain and the ΔtatC and ΔsufI mutant strains by integration of the complete lux operon from Photorhabdus luminescens into the 16S rRNA gene using a thermosensitive plasmid, p16Slux.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, we found that the wtL strain formed large numbers of foci and that some of them were not surrounded by neutrophils, which could make it possible for these bacteria to spread and cause systemic infection. The T3SS effectors YopH, YopE, and YopK are essential for the targeting of and escape from neutrophils during early infection (30). Our previous studies showed that the T3SS function was not affected in the ΔtatC mutant (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Given the presence of PMNs around bacterial foci in the cecal aggregates and the previously demonstrated importance of YopH and YopE for the antiphagocytic capacity of Y. pseudotuberculosis against PMNs (20,35,36), it was not surprising that these effectors together were found to be important for initial establishment of infection, which is a prerequisite for the development of persistent infection. Further, by using universal markers, we could not reveal any obvious effects on T cells, B cells, macrophages, and dendritic cells during the persistent state.…”
mentioning
confidence: 99%
“…Previously we have shown that Y. pseudotuberculosis efficiently evades neutrophilic attack in the early stages of infection and that mice with reduced numbers of neutrophils are more sensitive to initial bacterial colonization (32), indicating that neutrophil escape is an important feature of virulent Yersinia species. While it is well appreciated that Y. pseudotuberculosis resists phagocytic engulfment by both neutrophils and macrophages (33,34), less is known about how this pathogen faces the challenge posed by neutrophil degranulation.…”
mentioning
confidence: 99%